The influence of job resources on work engagement and visitors’ satisfaction at expo: a case of MAHA Expo 2018 / Nor Azmawati Husain … [et al.] - Husain, Nor Azmawati; Abas, Norlela; Norhisham, Norshiba; Ariffin, Nurul Azrin (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Visitor satisfaction is essential for every sector especially in mega events such as MAHA 2018. Many factors have been highlighted in influencing visitor satisfaction before including the roles of employees themselves. This study investigates the association of job resources such as skill discretion and co-workers support among employees at booths in MAHA 2018 visitor satisfaction specifically through work engagement (e.g. dedication and absorption). 99 onsite surveys were collected from employees and visitors at various booths at the MAHA 2018 event. Data was analysed using SPSS version 20 using multiple regression analysis. The study suggests that the dedication of employees mediates the relationship between skill discretion and visitor satisfaction. This supports the notions of employees’ work engagement especially the dedication aspect that crosses over to visitors and affect their satisfaction level.